Kajian Pola Sebaran Ritel Modern Terhadap Kawasan Permukiman Dan Reorganisasi Ruang Kota Di Kota Mataram - Fariz Primadi Hirsan; Sri Rahmi Yunianti; Febrita Susanti; Ima Rahmawati Sushanti (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2026)
Urbanization and population growth have accelerated urban spatial transformation, notably through the expansion of modern retail developments into residential neighborhoods. Beyond its economic significance, the proliferation of modern retail represents a process of urban spatial reorganization, involving changes in spatial functions and structures that do not necessarily conform to established planning frameworks. This study aims to analyze the spatial distribution patterns of modern retail in Mataram City and evaluate its impact on the structure of residential areas. The research employs a quantitative approach with an emphasis on Geographic Information System (GIS)-based spatial analysis. Primary data, consisting of the coordinates of modern retail locations, were collected through field surveys, while secondary data included base maps and demographic information. Data analysis utilized techniques such as Kernel Density Estimation, Hot Spot Analysis (Getis-Ord Gi)*, Network Analysis, and Overlay to assess compliance with the Regional Spatial Plan (RTRW) document. The analysis reveals that the distribution of modern retail in Mataram City shows a concentrated pattern along main roads. This pattern creates concentrated areas within the central city sub-districts, with a tendency for development to expand southward. Most residential areas are within the optimal service range (radius <500 meters), indicating functional efficiency. Although this expansion drives spatial reorganization, the majority of modern retail locations align with commercial zoning in the Regional Spatial Panning Document (RTRW), suggesting a harmony between the growth of the retail sector and formal urban planning.